Implementasi Peraturan Menteri Agama Nomor 31 Tahun 2020 Tentang Pendidikan Pesantren (Studi Kebijakan Pembelajaran Ilmu Nahwu Shorof Di Pondok Pesantren Subulus Salam Trenggalek) - Fara Fariha (CV. Publikasi Indonesia, 2022)
Pesantren education is very core and mandatory in relation to religious knowledge. For this reason, the Minister of Religion Regulation Number 31 of 2020 concerning Islamic Boarding Schools was issued which specifically regulates the course of education in an Islamic boarding school. Islamic boarding schools themselves use the yellow book curriculum and the Koran as their main educational foundation, but currently there are also Islamic boarding schools that have implemented general education in their pesantren. At the Subulus Salam Trenggalek Islamic Boarding School, it is mandatory to learn comprehensive nahwu shorof science from the lower middle class to the upper class. The Subulus Salam Trenggalek Islamic Boarding School itself has also implemented formal education to support student learning, such as PAUD, Raudlatul Athfal, Marosah Ibtida'iyah, Islamic Junior High School, Equality Package B and Package C, and also the Orphanage. This research approach is descriptive qualitative. The data in this study consisted of primary data obtained from interviews and secondary data obtained from documentation, archives, literature, and books related to the research focus. Data collection techniques used in the form of interviews, observations, and documentation as well as several supporting tools such as interview guidelines and other supporting tools. Data analysis techniques are carried out through the process of collecting data, presenting data, and drawing conclusions. This study was conducted to describe the implementation of the nahwu shorof science education policy in the subulus salam trenggalek Islamic boarding school. The results of this study indicate that the implementation of the Nahwu Shorof Science Learning Policy at the Subulus Salam Trenggalek Islamic Boarding School was carried out well but could not be optimal because there were still several obstacles. Therefore, maximum effort is needed in providing education with good cooperation and coordination between policy makers and policy implementers.